Observation of vertical coupling during a major sudden stratospheric warming by ICON and GOLD: a case study of the 2020/2021 warming event - Yiğit, Erdal; Gann, Ayden L.; Medvedev, Alexander S.; Gasperini, Federico; Wu, Qian; Sakib, Md Nazmus (Frontiers in Astronomy and Space Sciences, 2024)
The response of the thermospheric daytime longitudinally averaged zonal and meridional winds and neutral temperature to the 2020/2021 major sudden stratospheric warming (SSW) is studied at low-to middle latitudes (0 • -40 • N) using observations by NASA's ICON and GOLD satellites. The major SSW commenced on 1 January 2021 and lasted for several days. Results are compared with the non-SSW winter of 2019/2020 and pre-SSW period of December 2020. Major changes in winds and temperature are observed during the SSW. The northward and westward winds are enhanced in the thermosphere especially above ∼140 km during the warming event, while temperature around 150 km drops up to 50 K compared to the pre-SSW phase. 10 Changes in the zonal and meridional winds are likely caused by the SSW-induced changes in the propagation and dissipation conditions of internal atmospheric waves. Changes in the horizontal circulation during the SSW can generate upwelling at low-latitudes, which can contribute to the adiabatic cooling of the low-latitude thermosphere. The observed changes during the major SSW are a manifestation of long-range vertical coupling in the atmosphere.